Philosophy in science an historical introduction - Heller, Michael (Springer, 2011)
The traditional topics of the "philosophy of nature" space, time, causality, the structure of the universe are overwhelmingly present in our modern scientific theories. This book traces the complex paths that discussion of these topics has followed, from Plato and Aristotle, through Descartes, Leibniz, Kant and other great thinkers, right up to the relativistic cosmologies and the grand unified theories of contemporary science. In the light of this historical development, it becomes clear that modern science gives us not only a technological power over the world, but also a deeper understanding of physical reality. In this sense, science could be regarded as an heir to the traditional "philosophy of nature". Moreover, the reader will learn why science itself deserves to be the subject of philosophical reflection.